New solitary waveforms and their dynamics in the stochastic generalized Chen–Lee–Liu model - Ahmed M. Elsherbeny; Taher A. Nofal; Yakup Yıldırım; Ahmed H. Arnous (AIMS Mathematics)
This paper explores the dynamics of the generalized Chen-Lee-Liu equation, a fundamental model in nonlinear optics, extended to incorporate multiplicative white noise. By employing Itô calculus, the stochastic behavior of the system was is rigorously analyzed, providing insights into the effects of perturbations on soliton dynamics. The improved extended modified tanh-function approach was utilized to derive a variety of soliton solutions, including singular, dark, and bright solitons, as well as newly identified straddled solitons. This analytical approach highlights the transformative relationships between soliton types under specific conditions, expanding the spectrum of known solutions. The incorporation of multiplicative white noise reveals intricate changes in soliton stability, amplitude, and velocity, illustrating the interplay between deterministic and stochastic influences. These findings offer theoretical advancements in the understanding of soliton behavior in noisy environments and have practical implications for optical communication systems and nonlinear wave modeling. This study enriches the theoretical landscape of soliton dynamics and sets the stage for future research into stochastic soliton systems.